CURRENT STATE OF CONSUMPTION, POLLUTION AND PROTECTION OF WATER RESOURCES IN THE DEBED RIVER BASIN SYSTEM (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The current state of the Debed Rriver basin system has been analyzed and assessed, anthropogenic pressures on water resources have been discussed, the super objectives of the sphere have been analyzed and clarified mechanisms for effective use and protection of water resources have been proposed.
Keywords: water resources; water consumption; water intake; water supply and sanitation; water quality; quality; protection; Debed River basin system